Principles of tropical agronomy - Azam-Ali, S. N. (CABI, 2002)
This book is concerned with the principles by which crop management can influence how plants use environmental resources. It synthesizes current knowledge in plant physiology, environmental physics, soil science and climate to provide a framework for studying crop production in tropical environments.